Using ideal time horizon for energy cost determination - Hasan, Raed Abdulkareem; Abdulwahid, Hadeel W.; Abdalzahra, Arwa Sahib (College of Education, Al-Iraqia University, 2021)
In most optimal VM placement algorithms, the first step to determine the proper time horizon, T for the prediction of the expected maximum future load, L. However, T is dependent on the proper knowledge of the required time for servers to switch from their initial SLEEP/ACTIVE state to the next desired state. The activities implemented by this policy are (a) to relocate the VM from an encumbered server, a server that operates in an undesirably high regime with applications forecasted to rise their burdens to compute in the subsequent reallocation cycles; (b) to conduct VM migration from servers that operate within the undesirable regime to shift the server to a SLEEP mode; (c) putting an idle server to SLEEP mode and rebooting the servers from the SLEEP mode at high cluster loads. A novel mechanism for forwarding arriving client desires to the utmost suitable server is implemented; thus, in the complete system, balancing the requested load is possible.